The Phillips curve for the dollarized economy of Ecuador - Covri Rivera, Daniele (2021)
This paper consists of applying the Phillips curve for Ecuador in the period of dollarization. The data were adjusted for a structural break present at the beginning of the sample and cover a time horizon that goes from the first quarter of 2003 to the fourth quarter of 2015. The variables were contextualized to the Ecuadorian reality, but the core is based on the econometric estimation. The first part foresees ols regressions with adaptive expectations, and the unemployment and output gaps were obtained using a Hodrick and Prescott filter. The process was then repeated using instrumental variables with rational expectations and at the end three New Keynesian dsge models were also estimated. It was found that the Phillips curve is validated only with the unemployment gap, while inflation expectations are significant only in the multi-equation models that involve the output gap. In conclusion, policies that want to stimulate employment have a rising effect on prices, so this policy can be justified in recessive periods to avoid a possible deflation.